1999
DOI: 10.1063/1.370120
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional magnetophotonic crystals

Abstract: Two types of one-dimensional photonic crystals composed of magnetic and dielectric materials (magnetophotonic crystals) driven, respectively, by Kerr (reflection) and Faraday (transmission) modes were constructed. Their optical and magneto-optical (MO) properties were studied in detail to confirm our theoretical results showing the large Kerr and Faraday effects of the media originating in the localization of light. For the Kerr-mode operation, films with (SiO2/SiN)×k/Co/(SiN/SiO2)×k (k: number of layers) stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
137
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(143 citation statements)
references
References 4 publications
2
137
0
4
Order By: Relevance
“…This was shown recently by observation of giant Faraday effect in magnetic photonic crystals [3][4][5].…”
mentioning
confidence: 53%
“…This was shown recently by observation of giant Faraday effect in magnetic photonic crystals [3][4][5].…”
mentioning
confidence: 53%
“…In the p-in, p-out polarization combination, the nonmagnetic (crystallographic) SHG field E cryst 2ω originates from χ (2) zzz , χ (2) zxx , and χ (2) xxz elements of the χ (2)cryst tensor. The magnetization-induced SHG field E magn 2ω exp(iϕ M ) is coming from χ (2) xzzY , χ (2) zxzY , and χ (2) xxxY elements of the χ (2) and E magn 2ω are enhanced similarly due to the fundamental field localization.…”
Section: Mshg In Magnetophotonic Microcavitiesmentioning
confidence: 99%
“…Literal magnetophotonic crystals (MPC) formed of multilayer stacks of magnetic garnet -silicon oxide pairs were developed recently 3) . Both these classes of magnetic PBG structures show perspective linear magneto-optical properties: linear Faraday effect is strongly enhanced in magnetophotonic microcavities 2) and magnetophotonic crystals 3) . Meanwhile, mechanisms of this enhancement of Faraday rotation are different for MPM and MPC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that one-dimensional MPCs based on magnetic and nonmagnetic dielectric multilayers realize a huge Faraday rotation angle. [1][2][3][4][5] This MO enhancement originates from the localization of light at selected wavelengths in photonic band-gap structures. Similarly, MO cavities consisting of stacked layer structure enhance the MO effect by multiple re ections of light inside the structure.…”
Section: Introductionmentioning
confidence: 99%